Students' Spatial Ability During Geometry Learning through a Realistic Approach In Terms of Their Genetic Decomposition - Nugroho, Khathibul Umam Zaid; Sukestiyarno, YL; Hidayah, Isti (International Journal of Trends in Mathematics Education Research, 2023)
Geometry is a part of mathematics that students must learn. Spatial ability as a basic ability that students must have to learn more geometry. The realistic mathematical approach provides horizontal processing towards formal understanding. The purpose of this study is to interpret the characteristics of students' spatial abilities during learninggeometry through a realistic mathematical approach in terms of APOS Theory. This research uses quantitative qualitative and descriptive methods. The focus of this research is to explore students' spatial abilities after learning geometry through a realistic approach in understanding geometry concepts reviewed from APOS (Action-Process-Object-Schema) Theory. To comply with the COVID-19 health protocol, the implementation of learning was carried out online with as many as 30 students in the Mathematics Education Program in Rejang Lebong Regency, Bengkulu Province, Indonesia. This study also has exploratory characteristics. The researcher acts as a teacher as well as the main instrument in this study. Researchers use spatial ability test instruments to explore qualitative data. The test result data is used as the basis for determining the research subjects to be interviewed in depth to explore students' spatial abilities during geometry learning through a realistic mathematical approach. The subjects of this study were three students selected from three categories of test results, namely the high, medium and low groups of one person each. Interviews of subjects were conducted using whatsapp media via video call. These interviews are recorded to obtain complete and accurate data. Research data are analyzed through genetic decomposition analysis (description of their actions, objects, processes, schemes, and relationships that individuals have for concepts and principles in spatial geometry). The result of this study was that it was found that students had a mature scheme about the properties of building space. He was able to perform the tematization of objects about the diagonal of the plane and the diagonal of space can be represented in good mental activity, he was a student of the trance level. Inter students are able to carry out action-process-object-and schematic activities, but the embedding is incomplete. Intra students are able to do perceptions of space, but are unable to do interiorization and encapsulation so they fail to solve the given problem. The conclusion of this study is that there is an increase in the spatial understanding of students who are taught through a realistic mathematical approach. There are three levels of students' spatial ability after learning geometry through a realistic mathematical approach. Those are the trance level, the inter level and the lowest intra level.